Lermontov’s Borodino Strophe and Issues of Russian Verse Theory - Grinbaum, Oleg (Respectus Philologicus, 2012)
The paper considers several issues of Russian Verse Theory connected with the architectonics of Lermontov’s Borodino strophe. This rare and unique strophe is characterized by an odd number of lines (seven), peculiar rhyme, and mainly by the different number of syllables in its lines: five lines of the strophe contain nine syllables of iambic tetrameter, while the third and the seventh contain six syllables of iambic trimeter. Such a structure does not allow the use of traditional (statistical) methods of the study of verse rhythmics. To prove that, this paper describes the construction of “stress profiles” for the quatrain in iambic tetrameter, and shows that it is impossible to carry out this procedure for Lermontov’s Borodino strophe. Unlike the traditional approach, our method of rhythmic-harmonic precision imposes no restrictions on the architectonics of verse, which is why it is this method that underlies the analysis of the structural harmony of the Borodino strophe given in this paper. Our analysis compares the rhythmic-harmonic potential of the strophe and the actual values of the rhythmic harmony parameter with iambic and trochaic quatrains and with Onegin’s strophe in Pushkin’s verse. Another task of our work was a rhythmic-conceptual study of the “Borodino” text. This poem was published in 1837; together with the poem “On the Poet’s Death,” it immediately moved Lermontov to the forefront of Russian poets. The main result of our work consists in proving that in its structural-harmonic aspect, the Borodino strophe is unique and, moreover, it turns out to be the perfect verse construction for the expression of a mixed sublime-descending poetic mood: inspiration (in our case, a patriotic rise) and the following disappointment. Our study shows that Lermontov’s great poem “Borodino” not only passes “the trial of harmony with algebra,” but also, from the point of view of its single a rhythm-sense, stands near the best works of the first Russian poet, Pushkin.
Keywords: prosody; harmony; rhythm; mathematics